Calculating the Final Cost of Student Training by Activity Based Costing in School of Allied Medicine, Tehran University of Medical Sciences - Saman Ghasempour; Ramin Rahimniya; Zeynab Rajabnezhad; Hossein Dargahi (Tehran University of Medical Sciences, 2016)
Background and Aim: Today, regarding the role of accurate final information, and decision-making, designing and implementation of a sound costing system that can detect, identify and calculate the exact cost of the delivered services is of great importance. The aim of this study is to estimate the final cost of student education in the School of Allied Medicine, Tehran University of Medical Sciences, through Activity-Based Costing method in 2013. Materials and Methods: This research was a descriptive and applied study. The study population included School of Allied Medicine. The consumed costs in financial year 2012-2013 was investigated with costs classification, and finalized costs by activity based costing method. After identification of calculated costs and changed to allocation costs, The accumulated costs according to shared basic principle was given to all of delivered services. Finally, the finalized costs for student education based on the number and kind of courses collected and calculated by Excel software 2010. Results: The results indicated that the final cost for student education in PhD-level was 118,312,679 Rials, which was the highest amount, and was 76,714,824 Rials in MSc. level, and the lowest amount was related to BSc. student as 42,312,537 Rials. Conclusion: Paying attention to activity-based costing system with complete flexibility reveals the drawbacks of the traditional programs used by universities. The reason for higher costs in higher levels is due to the fewer number of students, particular facilities in these level and their own special expenses